DEVELOPMENT OF INTERCULTURAL COMMUNICATIVE COMPETENCE (Scientific journal of the Fergana State University, 2025)
In an increasingly interconnected world, building intercultural communicative competence (ICC) is essential for effective interaction among diverse cultures. This article examines the significance of ICC, highlighting its cognitive, affective and behavioral components. Through a literature review, key strategies for developing ICC are identified, including education and training, cultural immersion, active listening, reflection, and engagement in diverse communities. The findings underscore the importance of ICC in promoting understanding, tolerance, and personal growth in multicultural environments. As globalization continues to shape our interactions, fostering ICC will be crucial for success in both personal and professional domains.